Non-linear relationship between calf circumference and global cognition in Chinese population: a cross-sectional study of 12,102 Chinese older adults - Nie, Yuting; Gu, Cheng; Wu, Ruipeng; Gao, Fulin; Zhang, Le; Zhang, Yamin (Frontiers in Aging Neuroscience, 2025)
BackgroundLimited evidence exists regarding the relationship between calf circumference (CC) and global cognition in the Chinese population, with minimal research exploring potential sex disparities. Our goal was to investigate the correlation between CC and global cognition using data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), focusing specifically on sex variations.MethodsThe study participants were older adults who participated in the 2018 CLHLS survey. In this cross-sectional study, we employed multiple linear regression to examine the association between CC and global cognition. Smoothed curve fitting was used to explore the non-linear association between CC and global cognition. Furthermore, subgroup analyses were conducted to evaluate the reliability of the correlation between CC and global cognitive performance.ResultsIn total, 12,102 older adults were included in the study. A positive correlation was found between global cognition and CC (β = 0.42, 95% CI = 0.3-0.54, P < 0.001) after controlling for confounding factors. Further analysis revealed a non-linear relationship between CC and global cognitive performance. In the overall population, the inflection point for CC was 31 cm; a positive relationship was observed between CC and global cognition for CC values <31 cm (β = 0.177, 95% CI = 0.128-0.225, P < 0.001); however, this relationship disappeared for CC values ≥ 31 cm (β: −0.009, 95% CI = −0.04 to 0.023, P = 0.591). Furthermore, we identified sex-specific variations in the correlation between global cognitive performance and CC. Notably, among women with CC values <32 cm, a significant positive correlation was observed between CC and overall cognitive function. Conversely, for women with CC ≥ 32 cm, no significant association was found between CC and cognitive performance. Interestingly, no non-linear relationship was detected in males.ConclusionThis study demonstrated a non-linear relationship between CC and global cognition in older Chinese population. Furthermore, sex disparities are observed in the relationship between CC and global cognition, with a non-linear link evident in women but not in men. Older women with lower CC should actively participate in physical activity to maintain an appropriate CC and prevent cognitive decline.